2023
DOI: 10.1177/17539447231154654
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of intracoronary epinephrine for the management of the no-reflow phenomenon following percutaneous coronary interventions: a systematic-review study

Abstract: Background: Currently, no pharmacological or device-based intervention has been fully proven to reverse the no-reflow phenomenon. Objectives: To assess the efficacy and safety of intracoronary (IC) epinephrine in the management of no-reflow phenomenon following percutaneous coronary intervention (PCI), either as first-line treatment or after the failure of conventional agents. Design: Systematic review. Data sources and methods: PubMed and Scopus databases were systematically searched up to 28 May 2022, with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 18 publications
(51 reference statements)
0
3
0
Order By: Relevance
“…This outcome reflects the successful restoration of myocardial perfusion and symptom relief, contributing to the overall well-being of patients (Abu Arab et al, 2016;Aksu et al, 2015;Poon et al, 2013). The three-month follow-up data reveal encouraging results, with 90% of patients showing no re-flow recurrence (Jafari Afshar et al, 2023). Additionally, a notable improvement in left ventricular ejection fraction (LVEF) was observed in 65% of patients.…”
Section: Discussionmentioning
confidence: 83%
“…This outcome reflects the successful restoration of myocardial perfusion and symptom relief, contributing to the overall well-being of patients (Abu Arab et al, 2016;Aksu et al, 2015;Poon et al, 2013). The three-month follow-up data reveal encouraging results, with 90% of patients showing no re-flow recurrence (Jafari Afshar et al, 2023). Additionally, a notable improvement in left ventricular ejection fraction (LVEF) was observed in 65% of patients.…”
Section: Discussionmentioning
confidence: 83%
“…On the other hand, intra-coronary epinephrine showed better efficacy and improvement in TIMI flow, MBG, and resolution of ST-segment elevation with a signal for reduction in adverse clinical outcomes at 30 days [ 42 , 43 , 44 ]. A recent network meta-analysis of 41 randomised control trials (RCTs) and 4069 patients suggested that anisodamine, a muscarinic cholingeric antagonist, and SNP improve coronary flow and MACE outcomes compared to other IC agents or control groups [ 45 ].…”
Section: Treatments For Microvascular Obstructionmentioning
confidence: 99%
“…However, despite successful revascularization, some patients may develop a phenomenon known as "no-reflow," which refers to a persistent impairment of coronary blood flow despite restoring epicardial vessel patency. No reflow can lead to poor clinical outcomes and is associated with higher mortality risk (Niccoli et al, 2009). Various treatment options have been explored for noreflow during primary PCI, including intracoronary epinephrine, which has been proposed as a potential treatment to improve coronary blood flow.…”
Section: Introductionmentioning
confidence: 99%